PENDAMPINGAN KEGIATAN PEMASARAN UMKM PRODUK KERIPIK SINGKONG DI RT 02/RW 01 DESA WARINGIN JAYA KABUPATEN BOGOR - Suharti, Titing; Firdaus, M. Azis; Yudhawati, Diah; Sundarta, M. Imam; Hurriyaturrohman, Hurriyaturrohman; Kusumah, Anuraga (LPPM Univ. Ibn Khaldun Bogor, 2022)
The implementation of Large-Scale Social Restrictions (PSBB) as a result of the COVID-19 pandemic since March 2020 has directly suppressed the rate of economic growth, the COVID-19 pandemic has not only hit the global economy but also in Indonesia. However, the economic sector must continue to rotate, including MSME activities. Various efforts and ways to restore the MSME sector continue to be carried out until now because MSME actors are the spearhead of economic movement in society. The purpose of this service is to provide a digital understanding of business in terms of marketing activities for cassava chip products to MSME actors in Waringin Jaya Village, Bogor Regency. Analysis of partner needs, Lectures and discussions, and Tutorials. The cassava chip SMEs in Waringin Jaya Village can understand the importance of online marketing and understand how to make packaging which is expected to increase the sales volume of cassava chips.